TRACKING CONTROL FOR ELECTRO-OPTICAL SYSTEM IN VIBRATION ENVIROMENT BASED ON SELF-TUNING FUZZY SLIDING MODE CONTROL - Kim, Duyen Ha Thi; Manh, Tien Ngo; Nhu, Chien Nguyen; Hoang, Viet Do; Thu, Huong Nguyen Thi (Journal of Computer Science and Cybernetics, 2019)
The paper presents a new method for tracking control of EOTS (Electro-Optical Tracking System) operating in mobile environment such as ship, air plane, tank and so on. This makes the base body of the EOTS has angular motion. The control alogorithm used in this paper is adaptive fuzzy sliding mode. The overall control is built and simulated in Matlab and compared with a sliding mode controller and a conventional PID controller. The simulation result illustrated the effectiveness of the proposed controller